An efficient eigenspace updating scheme for high-dimensional systems - Gangl, Simon; Mongus, Domen; Žalik, Borut (Zielona Góra: Uniwersytet Zielonogórski)
Systems based on principal component analysis have developed from exploratory data analysis in the past to current data processing applications which encode and decode vectors of data using a changing projection space (eigenspace). Linear systems, which need to be solved to obtain a constantly updated eigenspace, have increased significantly in their dimensions during this evolution.
Keywords: eigenspace updating; projection space; data compression; principal component analysis (PCA)